What Is It to Incorporate an Incentive into a Maxim? - Favaretto, Martina (Studia Kantiana, 2023)
The Incorporation Thesis makes it clear that, according to Kant, we are not caused to act by this or that incentive, but rather we let it move us by incorporating it in our maxim. However, Kant does not provide us with a more detailed account of incorporation in which he specifies what incorporation amounts to, why it is necessary, and how it works. In this paper, I aim to lay the foundation for such an account by appealing to Kant’s notion of interest. I argue that to incorporate an incentive into a maxim amounts to forming an interest on the basis of that incentive. Moreover, I argue that Kant’s notion of interest allows for the idea that acting on an inclination does not necessarily involve taking that inclination as the object of one’s reflection.